NAD Modulates DNA Methylation and Cell Differentiation - Simone Ummarino; Clinton Hausman; Giulia Gaggi; Lucrezia Rinaldi; Mahmoud A. Bassal; Yanzhou Zhang; Andy Joe Seelam; Ikei S. Kobayashi; Marta Borchiellini; Alexander K. Ebralidze; Barbara Ghinassi; Bon Q. Trinh; et al. (Cells, 2021)
Nutritional intake impacts the human epigenome by directing epigenetic pathways in normal cell development via as yet unknown molecular mechanisms. Consequently, imbalance in the nutritional intake is able to dysregulate the epigenetic profile and drive cells towards malignant transformation. Here we present a novel epigenetic effect of the essential nutrient, NAD. We demonstrate that impairment of DNMT1 enzymatic activity by NAD-promoted ADP-ribosylation leads to demethylation and transcriptional activation of the CEBPA gene, suggesting the existence of an unknown NAD-controlled region within the locus. In addition to the molecular events, NAD- treated cells exhibit significant morphological and phenotypical changes that correspond to myeloid differentiation. Collectively, these results delineate a novel role for NAD in cell differentiation, and indicate novel nutri-epigenetic strategies to regulate and control gene expression in human cells.